Engrailed homeoprotein blocks degeneration in adult dopaminergic neurons through LINE‐1 repression. (25th June 2018) - Blaudin de Thé, François‐Xavier; Rekaik, Hocine; Peze‐Heidsieck, Eugenie; Massiani‐Beaudoin, Olivia; Joshi, Rajiv L; Fuchs, Julia; Prochiantz, Alain
Abstract: LINE‐1 mobile genetic elements have shaped the mammalian genome during evolution. A minority of them have escaped fossilization which, when activated, can threaten genome integrity. We report that LINE‐1 are expressed in substantia nigra ventral midbrain dopaminergic neurons, a class of neurons that degenerate in Parkinson's disease. In Engrailed‐1 heterozygotes, these neurons show a progressive degeneration that starts at 6 weeks of age, coinciding with an increase in LINE‐1 expression. Similarly, DNA damage and cell death, induced by an acute oxidative stress applied to embryonic midbrain neurons in culture or to adult midbrain dopaminergic neurons in vivo, are accompanied by enhanced LINE‐1 expression. Reduction of LINE‐1 activity through (i) direct transcriptional repression by Engrailed, (ii) a siRNA directed against LINE‐1, (iii) the nucleoside analogue reverse transcriptase inhibitor stavudine, and (iv) viral Piwil1 expression, protects against oxidative stress in vitro and in vivo . We thus propose that LINE‐1 overexpression triggers oxidative stress‐induced DNA strand breaks and that an Engrailed adult function is to protect mesencephalic dopaminergic neurons through the repression of LINE‐1 expression. Synopsis: Oxidative stress induces excessive DNA damage through the induction of LINE‐1 retrotransposon expression. Conversely, anti‐LINE‐1 strategies, including homeoprotein Engrailed direct repressor activity, prevent dopaminergic neuron loss. Inhibiting LINE‐1 expression or activity may thus be considered for the development of novel therapeutic strategies in neurology. Full length LINE‐1 retrotransposons are expressed in adult mouse midbrain dopaminergic neurons. Oxidative stress‐induced DNA strand breaks formation follows an increase in LINE‐1 expression. LINE‐1 endonuclease ORF2p participates in the formation of DNA strand breaks. The homeoprotein transcription factor Engrailed is a direct repressor of LINE‐1 expression. Anti‐LINE‐1 strategies prevent dopaminergic neurodegeneration in acute oxidative stress and chronic Parkinson's disease models in mice. Abstract : The transcription factor Engrailed protects mesencephalic dopaminergic neurons by repressing the expression of the retrotransposon element LINE‐1.